1985
DOI: 10.1038/318186a0
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin causes short-lived inhibition of bradykinin-stimulated prostacyclin production in man

Abstract: Acetylsalicylic acid (aspirin) inhibits prostanoid synthesis by irreversible acetylation of fatty acid cyclooxygenase (EC 1.14.99.1). It thereby inhibits synthesis of pro-aggregatory thromboxane A2 (TXA2) by platelets and is widely used in the treatment and prophylaxis of vascular disease. Its efficacy, however, may be reduced since it also inhibits formation of prostacyclin (PGI2) which is a vasodilator and anti-aggregatory agent. There is uncertainty over the optimum dose regimen for aspirin since although i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 27 publications
4
82
0
Order By: Relevance
“…It has been variously suggested that lower doses of aspirin than those of proven efficacy could be either more or less effective than standard doses (see Ritter, 1988 for a review of these arguments). The present study emphasises the importance of dose interval rather than absolute dose (Moncada, 1982;Heavey et al, 1985), by demonstrating that it is possible to use a dose of aspirin (600 mg), that has proved effective in clinical trials, in such a way that thromboxane biosynthesis is profoundly and persistently inhibited but prostacyclin biosynthesis is unimpaired for much of the dose interval. In this context it is noteworthy that in a recent study of aspirin given on alternate days to apparently healthy American physicians, the rate of myocardial infarction was halved (The Steering Committee of the Physicians' Health Study Research Group, 1988), whereas a study in which aspirin was given more frequently (and in some instances in an enteric coated formulation) to British physicians, showed no effect on myocardial infarction rate (Peto et al, 1988 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been variously suggested that lower doses of aspirin than those of proven efficacy could be either more or less effective than standard doses (see Ritter, 1988 for a review of these arguments). The present study emphasises the importance of dose interval rather than absolute dose (Moncada, 1982;Heavey et al, 1985), by demonstrating that it is possible to use a dose of aspirin (600 mg), that has proved effective in clinical trials, in such a way that thromboxane biosynthesis is profoundly and persistently inhibited but prostacyclin biosynthesis is unimpaired for much of the dose interval. In this context it is noteworthy that in a recent study of aspirin given on alternate days to apparently healthy American physicians, the rate of myocardial infarction was halved (The Steering Committee of the Physicians' Health Study Research Group, 1988), whereas a study in which aspirin was given more frequently (and in some instances in an enteric coated formulation) to British physicians, showed no effect on myocardial infarction rate (Peto et al, 1988 …”
Section: Discussionmentioning
confidence: 99%
“…Effects of bolus dose aspirin or salicylate on stimulated prostanoid biosynthesis The protocol for these studies was similar to that described previously (Heavey et al, 1985). Briefly, each subject was infused for 10 min with bradykinin ((Sigma Chemical Co., Poole, UK): O.8-1.2 ,ug kg-1 min-' intravenously as individually tolerated, with the same subject receiving the same dose on every occasion) before and 0.5, 1.5, 3 and 6 h after an intravenous bolus dose (600 mg) of sodium salicylate or aspirin (EgicJoulie).…”
Section: Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, chewable ASA (Bayer, Morristown, NJ) in one of four doses (81, 648, 972, 1,944 mg) was given orally in random order. Thirty minutes after the administration of ASA, when the endothelium-derived prostacyclin is maximally inhibited (26), the response to dose-dependent application of ACh (1%) at the corresponding area of the opposite forearm was recorded. All tests were performed after an acclimatization period of at least 30 min.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…We have chosen a high dose of aspirin, a potent inhibitor of cyclo-oxygenase, and have administered the drug in soluble form to improve bioavailability (Martindale, 1981). The 1 h gap between dosing and repeat cough challenge was sufficient to allow adequate absorption of the drug (Martindale, 1981) and ensured that repeat cough challenge was performed at the time of maximal cyclo-oxygenase inhibition (Heavey et al, 1985). Systemic administration of cyclo-oxygenase inhibitors to experimental animals also inhibits pulmonary prostanoid production of this time-point (Dworski et al, 1989;Snapper et al, 1983).…”
Section: Discussionmentioning
confidence: 99%